PERSUASIVE STRATEGIES USED BY THE CANDIDATES OF GOVERNOR OF JAKARTA IN THE ELECTION DEBATE 2017 ON MATA NAJWA - Yenni Rofina Simanjuntak; I Wayan Dirgayasa; Anni Holila Pulungan (Universitas Negeri Medan, 2019)
This research dealt with the persuasive strategies used by the candidates of the governor of Jakarta. The objectives of this study were to investigate the types of persuasive strategies used by the candidates of governor of Jakarta in the election debate on Mata Najwa 2017. The data were obtained from the persuasive strategies utterances of the candidates of Governor of Jakarta on Mata Najwa. This research applied qualitative research design. The data were collected through observation by taking video recording. The findings of this study showed that there were six strategies of persuasive strategies that utilized by the candidates if governor of Jakarta, they are consistence, authority, social-evidence, reciprocal, preference and rareness strategy. Keywords: Persuasive Strategy, Mata Najwa, Governor, Election Debate